Peranan Analisis Jabatan terhadap Kinerja Pegawai pada Sekretariat Daerah Kabupaten Batu Bara - Oriza Sativa; Siti Mardiana; Maksum Syahri Lubis (Universitas Medan Area, 2022)
The purpose of this study is to analyze and describe how the role of job analysis on employee performance at the Regional Secretariat of Batu Bara Regency. As well as to analyze the constraints in job analysis on employee performance at the Regional Secretariat of Batu Bara Regency. This type of research is a qualitative research. Collecting data through methods from observations, interviews and documentation. The results showed that the application of job analysis to employee performance in the form of positions at the Regional Secretariat of Batu Bara Regency was good. The contents of the position in the form of tasks, jobs, responsibilities, authorities and working conditions at the Regional Secretariat of Batu Bara Regency have been carried out according to the results of the job description. In addition, the use of the contents of the position as the basis for implementing the work environment as well as the basis for meeting equipment needs, has also been carried out. However, the application of job analysis to employee performance in the form of position qualifications at the Regional Secretariat of Batu Bara Regency has not been optimal. There are still employees who are placed not in accordance with the educational background that is placed. The role of job analysis on employee performance at the Regional Secretariat of Batu Bara Regency has not been achieved optimally. Application of Application Analysis that is applied in accordance with predetermined qualifications. In its implementation, the Regional Secretariat of Batu Bara Regency is still experiencing problems with the limited number of employees.